Sex-based differences in cardiac ischaemic injury and protection: therapeutic implications - Ostadal, B; Ostadal, P (British journal of pharmacology, 2014)
Ischaemic heart disease (IHD) is the most frequent cause of mortality among men and women. Many epidemiological studies have demonstrated that premenopausal women have a reduced risk for IHD compared with their male counterparts. The incidence of IHD in women increases after menopause, suggesting that IHD is related to declining oestrogen levels. Experimental observations have confirmed the results of epidemiological studies investigating sex-specific differences in cardiac tolerance to ischaemia. Female sex appears also to favourably influence cardiac remodelling after ischaemia/reperfusion injury. Furthermore, sex-related differences in ischaemic tolerance of the adult myocardium can be influenced by interventions during the early phases of ontogenetic development. Detailed mechanisms of these sex-related differences remain unknown; however, they involve the genomic and non-genomic effects of sex steroid hormones, particularly the oestrogens, which have been the most extensively studied. Although the protective effects of oestrogen have many potential therapeutic implications, clinical trials have shown that oestrogen replacement in postmenopausal women may actually increase the incidence of IHD. The results of these trials have illustrated the complexity underlying the mechanisms involved in sex-related differences in cardiac tolerance to ischaemia. Sex-related differences in cardiac sensitivity to ischaemia/reperfusion injury may also influence therapeutic strategies in women with acute coronary syndrome. Women undergo coronary intervention less frequently and a lower proportion of women receive evidence-based therapy compared with men. Although our understanding of this important topic has increased in recent years, there is an urgent need for intensive experimental and clinical research to develop female-specific therapeutic strategies. Only then we will be able to offer patients better evidence-based treatment, a better quality of life and lower mortality.
Keywords: androgeny; Heart; reperfuzní poškození myokardu; Myocardial Reperfusion Injury; Myocardium; srdce; Evidence-Based Medicine; Female; náchylnost k nemoci; medicína založená na důkazech; Androgens; estrogeny; mužské pohlaví; Estrogens; myokard; Sex Characteristics; lidé; pohlavní dimorfismus; Cardiovascular Agents; Myocardial Ischemia; ischemická choroba srdeční; ženské pohlaví; zvířata; Humans; Acute Coronary Syndrome; kardiovaskulární látky; Disease Susceptibility; Male; Animals; akutní koronární syndrom